Externality Analysis of Laying Hens on The Community in Padakkalawa Village - R. Rusny; A. Astati; Khaerul Anwar; Mashuri Masri (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
Carrying out a business activity in the small and large-scale chicken farming sector certainly has externalities for other people and the surrounding environment. An externality is an impact (positive or negative) on the existence of a business which is a necessity that economic actors need to know. If the impact is detrimental, then it is called a negative externality. On the other hand, if the impact is favorable, it is called a positive externality. The problem of externalities is related to the problems of justice and welfare that occur in society. People's welfare can be measured by their income. Community income is the flow of money that flows from the business world to the community in the form of wages and salaries, interest, rent, and profits. The purpose of this study was to determine the externalities of laying hens to the community in Padakkalawa Village. The research used is descriptive quantitative, namely the process of finding knowledge that uses data in the form of numbers as a tool to analyze information. The results showed that the negative externality caused by laying hens is environmental pollution, while the positive externalities caused by laying hens are absorbing labor, creating new business opportunities, and the availability of manure.